Pemeliharaan Hubungan Antara Anak Dengan Orang Tua Berstatus Narapidana Di Dalam Lapas - Sahfitri, Dwina; Rahardjo, Turnomo (Interaksi Online, 2021)
Family communication can be changed when one family member, such as parents, either father or mother, is involved in a criminal case and goes to the Correctional Institution. The background of the study is the problems experienced by the prisoners' family that have an obstacle in communicating between parents and children with the limited communication facilities, and the negative impacts of parents' detention towards children. This study aims to give a reference from experience in relationship maintenance between children and parents with prisoners status in the Correctional Institution using the interpretive paradigm and a phenomenological approach. The data collection technique used was an in-depth interview. The theory used in this study was the Relationship Maintenance Theory. The results of the study reveal that in this case, parents have a strategy in having relationship maintenance by emphasizing on fun interaction strategy, guaranteed commitment, mutual support, affection, and good conflict management. The intensity of communication conducted by the prisoners and children is relatively low, but the prisoners realize the importance of maintaining communication quality. The openness conducted by the parents is limited to criminal cases and try to protect the child's feeling by making a positive atmosphere during the interaction. Parents build perceptions for their children to accept the cases. The children prove that parents' criminal cases do not impact education by giving support and affection to the parents while serving a detention period in the Correctional Institution. The children try to understand the conditions between parents, so the relationship is stable and maintained.